Pengembangan Sumber Daya Manusia Melalui Knowledge Management - Puput Mulyono; Singgih Purnomo (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
This research shows how a computerized change framework can be realized in human and information technology environments. This includes consideration of innovations and tools used in subsequent changes. The aim of this research is to investigate how industrial and organizational psychology can work together with information management to achieve organizational goals. This investigation is based on a proper audit. Through this strategy, researchers collect several multidisciplinary distributions from multidisciplinary journals. Therefore, in our opinion, taking these important components into account, we view proper auditing as a reasonable strategy that combines these components while avoiding the tendency for researcher subjectivity. Based on the research results obtained, industrial and organizational psychology and information management have empowered organizations to utilize innovation in managing information, which in turn, makes a difference in the progress of human resource development. Innovation has promoted knowledge collection, capacity and sharing, which is an important perspective of informatics management. However, there also seem to be challenges in implementing innovations in the field of industrial and organizational psychology.